The analysis of electrolyte chemistry pictorial material in lower secondary chool chemistry textbooks in Slovenia based on developed quality criteria - Zupanc, Nina; Devetak, Iztok (Scientia in educatione, 2021)
The textbook as a learning tool and learning resource contributes significantly to the effectiveness of the teaching or learning process itself, while at the same time promotes and facilitates independent learning. The main purpose of this research was to develop quality criteria after which textbooks for Chemistry in lower secondary school were evaluated. This paper presents the analysis of electrolyte chemistry pictorial material presented in chemistry textbooks. When it comes to validating textbooks in Slovenia, there are no unified criteria. The development of the criteria included an overview of the objectives set in the chemistry curriculum. Criteria were made for textbooks used in 8th and 9th grade of lower secondary school (students age 13–15 years). Chemistry textbooks were validated in the school year 2018/2019. When analysing criteria related to textbook representations, the sub-microscopic representations and hybrid representations are the least common features in the textbooks.